Belonging to nowhere: a psychological study of alienation and estrangement in Ramabai Espinet's “The Swinging Bridge” (2003) - Yahya, Salam Hussein; Mani, Manimangai; Bahar, Ida Baizura; Awang, Mohammad Ewan (Academy Publication, 2022)
Diaspora communities feel alienated because they cannot decide which space they belong to. The notions of identity and home are problematized and characterized by a sense of continuity and discontinuity, a conflict of location and dislocation and a process of hybridization. Espinet's The Swinging Bridge (2003) resembles outstanding indication of the psychological conflict that happens in the mind of the diaspora. Feelings, homes and identities are indeed swinging and cannot be certain to belong to a certain space or time. The question that is raised in this paper shows that there is no fixed home for a diaspora to belong to. This is due to a psychological clash between homes, identities, cultures, politics and many other factors that reconstruct and help in the formation of a hybrid identity that belongs to none in particular and cannot be accepted in all. So, this identity starts swinging between homes and cultures. The idea of 'bridge' in Espinet's The Swinging Bridge, is no more than an illusion and a dream that the writer tries to present as a solution for this dilemma of estrangement.